2019
DOI: 10.1590/1678-5150-pvb-6373
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for prevention and control of poisoning by sodium monofluoroacetate (MFA)-containing plants in ruminants

Abstract: Monofluoroacetate (MFA)-containing plants cause sudden death associated with exercise in ruminants, and are responsible for significant losses in Brazilian livestock, estimated at 500,000 bovine deaths annually. Most of the times, the control and treatment of this type of poisoning are not efficient, because disease evolution is superacute, usually causing the death of the animal. Due to the difficulty in controlling this intoxication, several studies have suggested alternatives to prevent it, mainly by making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…According to Pessoa et al (2019), in Brazil, there are about 131 species of toxic plants, divided into 79 genera. Some plants are so toxic that they can even cause sudden death due to the monofluoroacetate compound (MFA), among these plants the family stands out: Rubiaceae, Malpighiaceae, and Bignoniaceae (Arruda et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to Pessoa et al (2019), in Brazil, there are about 131 species of toxic plants, divided into 79 genera. Some plants are so toxic that they can even cause sudden death due to the monofluoroacetate compound (MFA), among these plants the family stands out: Rubiaceae, Malpighiaceae, and Bignoniaceae (Arruda et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Fencing off areas to prevent animals from accessing the plant is the most effective preventive measure, and animals that have consumed the plant should not be subjected to exercise. The use of bacteria that hydrolyze fluoroacetate to prevent poisoning has been experimentally proven but is not being used under field conditions ( Silva et al, 2016 ; Pessoa et al, 2019 ).…”
Section: Poisonous Plants In South Americamentioning
confidence: 99%
“…The treatment of poisoning by MFA and other plants having the same intoxication principle is challenging for physicians and veterinarians (Pessoa et al 2019). It has been reported that magnesium chloride (MgCl 2 ) at a dose of 50mg/kg is able to reverse the clinical condition of 90% of mice poisoned with 15mg/kg of MFA (Pereira & Pereira 2005).…”
Section: Introductionmentioning
confidence: 99%